Selection of local isolates of the genus Trichoderma for use in the control of wilt diseases and Damping off eggplant in Hama. - سليمان, شادي; موسى السمارة,; محمد أحمد ,; نوال علي , (Latakia University Journal -Biological Sciences Series, 2024)
Trichoderma is a fungal species used in the biological control of soil-borne fungal plant diseases. The research aimed to conduct a field survey of the genus Trichoderma in Hama governorate in order to determine the most efficient local isolates in controlling wilting and Damping off diseases on eggplant plants caused by Fusarium oxysporum and Rhizoctonia solani in laboratory conditions to be adopted in the mass prodaction of Trichoderma fungus. The results showed the isolation of 76 local isolates of the genus Trichoderma from 100 soil samples that were collected from the fields of the areas of Hama Governorate, in addition to isolating and identifying the pathogens tested from samples of infected eggplant roots and testing their pathogenicity. A series of efficiency tests were conducted, where the linear growth rate of each of the tested isolates was calculated, and the average linear growth speed of all isolates was 17.2 ± 0.3 mm / day. isolate and the rest of the isolates were excluded, a test of the degree of fungal antagonism with laboratory tested pathogens was performed; The ability of all tested isolates to antagonize pathogens was shown to varying degrees and ranged from 1 to 2.67 degrees on the Bell scale, and ten tested isolates outperformed the rest of the isolates by obtaining the highest degree of fungal antagonism with each of the pathogens (and it was between 1 to 1.33 degrees), and the results of the laboratory inhibition ratio test showed the ability of these ten isolates to inhibit the growth of pathogens with an inhibition rate of 69.99% for Fusarium oxysporum and 49.49% for Rhizoctonia solni. The ten tested isolates were able to produce abundant quantities of conidia, and their production ranged from 3.33 * 109 to 15.33 * 109 spores / gram, and outperformed both isolate No. 25 (15.33 * 109 spores / gram) and isolate No. 57 (6*109 spores / g) over the rest of the ten isolates in the production of conidia.